Programação para Jovens: Conteúdos, Atividades Estratégias e Ferramentas - Nuno Filipe Gomes dos Santos (2017)
Computer programming is an increasingly important competence in the training of a person, particularly young people. More than enabling for a better use of the enormous capacity and computational functionalities available today, it allows itself to develop the logical reasoning added to the capacity of problem solving. As such, programming education has been delivered to increasingly young people and young people from all over the globe, with various initiatives such as code.org, Kodu Game Lab, Hour of Code, Khan Academy and new tools for Teaching programming like Scratch, Alice or ToonTalk. These tools and technologies are used in curricular and extracurricular contexts, at school and at home, with appropriate adaptations in terms of content, activities, teaching / learning strategies and programming tools. Some countries have clearly distinguished themselves in this theme, both by advances in the teaching of technology and by the implementation, in their official curricular plan, of programming teaching. The UK, for example, has implemented the programming teaching program in the 2014 school year. The reality in Portugal although similar, there are still specific needs. The educational offer consists of Information Technology and Computing (basic education) and Computer Applications B (secondary education), Whose curricula can be improved, and the existence of these disciplines typically differs according to the educational offer of each school, Motivating or not, the students who ambition to follow technological areas in higher education. In this context, national and international, it was intended to begin by developing a set of didactic units (contents and activities) for students and teachers, as well as a set of strategies, goals, educational and pedagogical objectives for the teaching of programming to children and young people . Studies of the University of Minnesota report that time flies when students have fun in a study that relates the use of technology to cognitive absorption, as such the construction of this work was shaped by the preference of students. In order to avoid extra conditioning to students' learning, it contributes with content in Portuguese, Are still selected, configured and integrated a set of programming tools, using the state of the art of the area. This dissertation aims at the development of contents and activities, strategies and tools, for the teaching of programming to young people between 12 and 18 years of age, in Portuguese language.